Three new species of ischnoceran lice (Psocodea: Phthiraptera) from birds in China, with a key to the Lagopoecus-group of genera - Daniel R. Gustafsson; Zhu Li; Chunpo Tian; Mengjiao Ren; Xiuling Sun; Fasheng Zou (European Journal of Taxonomy)
Three new species of chewing lice (Psocoptera: Phthiraptera: Ischnocera) are described from hosts in China based on specimens deposited at the Natural History Museum of China. Galliphilopterus latifrons sp. nov. is described from Arborophila gingica (Gmelin, 1789) as the second known species of this genus. The relationships of the genus Galliphilopterus are discussed, and it is suggested this genus is close to Mulcticola Clay & Meinertzhagen, 1939. Lagopoecus liui sp. nov. is described from Lophura nycthemera (Linnaeus, 1758). Species groups within Lagopoecus Waterston, 1922 are suggested, based on a partial morphological review of the genu. A key to the species groups of Lagopoecus and presumed closely related genera is provided. Turdinirmus calleipus sp. nov. is described from specimens that likely constitute stragglers, and the natural host of this species is here considered unknown.